Uptake of HIV Testing Services through Assisted Partner Notification (APN) among Men in Wakiso District - Simons Ezajobo; Mary Odiit; Eve Namitala; Violette Nabatte; Christopher Ddamulira; Audrey Steenbeek; Bob Bortolussi; Noni MacDonald. (Open Access Journal of Disease and Global Health, 2025)
Background: In Uganda, Human Immunodeficiency Virus (HIV) testing amongst men remains suboptimal despite efforts like Assisted Partner Notification (APN), undermining national efforts to contain the HIV pandemic. Thus, this study examined both barriers and facilitators to HIV testing amongst men in Wakiso District, Uganda. Methods: A narrative design and in-depth interviews were used with 16 adult men and two health workers from Entebbe Regional Referral Hospital, Wakiso and Kajjansi Health Centre IVs in Wakiso District, Uganda. Purposive sampling was used to choose the health facilities and recruit participants for the study. Transcripts were transcribed verbatim and analyzed through content analysis using NVIVO software. Results: Participants perceived HIV testing under APN as beneficial due to: its privacy and confidentiality, convenience and efficiency, personal empowerment and potential for saving lives. Participants believed that APN enables early detection of HIV infections, early treatment initiation and better outcomes. Participants reported the desire to know their status as a major driver to accessing HIV testing services. On the contrary, fear for consequences such as trauma, stigma, anxiety, stress, blame and lifetime treatment were reported as barriers to HIV testing services. These fears were most times experienced immediately after notifica- tion. Male participants were not comfortable with phone call notification but instead preferred joint notification where the female spouse together with the health worker notified them together. Conclusion: This study demonstrated that HIV testing was perceived to be beneficial since its enabled participants to know their HIV status and hence, plan better for health living with their spouses. However, barriers such fear for early death, life-time treat- ment, family breakdown, blame and stigma among others hindered uptake of the services. Joint notification was the most preferred method identified by male participants since it ensured that both the female spouse and health worker were present at the time of notification. Therefore, there is need for sensitization of males about HIV testing to eliminate these barriers to HIV testing services. In addition, joint notification should be encouraged since the health worker is able to counsel the male participants on HIV related matters hence encouraging them to take the service.